المؤسسات الدينية ودورها في تطور التشريعات القانونية (التلقيح الاصطناعي مع التبرع بالحيوانات المنوية أنموذجــاً) - طعمة اكرم حياوي; عبد الحسن علي عبد الصاحب (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
Wealth and children are [but] adornment of the worldly life. But the enduring good deeds are better to your Lord for reward and better for [one’s] hope. (Surah Al-Kahf 46). Since humans are inherently inclined to love children and consider them a necessary complement to the beauty and adornment of the world, we can observe this through the request made by some prophets, such as Prophet Zakariah (peace be upon him), who supplicated to the Almighty, asking for righteous offspring. The occurrence of legitimate marital relations (marriage) is followed by reproduction. However, there can be reasons between spouses that hinder their ability to conceive, such as infertility or the inability to conceive due to weak sperm. Since Islam is considered a comprehensive religion that cares about all aspects of human life, including matters related to infertility and its treatment, Islamic teachings allow for the search for solutions and treatments for infertility as long as they are permissible and compliant with religious rulings and moral values. The field of medicine has witnessed significant advancements in the treatment of infertility and providing care for patients Those who are unable to conceive naturally often explore the role of religious institutions in developing legal regulations, particularly regarding issues such as artificial insemination and sperm donation. The research investigates the extent to which religious institutions contribute to the development of legal legislation in these modern methods of reproduction and the preservation of family unity, while also highlighting the stance of Islamic law on the use of these contemporary means of reproduction and maintaining family cohesion.